The importance of in-country African instructors in International experiential training programs; a qualitative case study from the university of Minnesota - Faith Nawagi; Aruna Raman (BMC Medical Education, 2023)
Abstract Background For effective delivery of international experiential training programs, many universities in the global north, have created partnerships with universities in the global south especially in Africa to enhance their capacity and diversity of learning for their students. However, there is hardly any literature that exhibits the importance of African instructors in international experiential learning programs. This study aimed at establishing the importance of African instructors in international experiential learning programs. Methods This was a qualitative case study that examined the importance of instructors and experts from Africa in influencing student learning processes and outcomes in the GCC 3003/5003 - Seeking Solutions to Global Health Issues. Semi-structured interviews with (2) students, (2) University of Minnesota lead faculty for the course, and (3) in-country instructors/experts from countries in East Africa and the Horn of Africa were conducted. Data was analyzed thematically. Results Four themes were identified: (1) Filling gaps in knowledge, (2) Orchestrating partnerships for practical exposure, (3) Improving the quality of training, and (4) orchestrating professional personal growth for students. The African in-country course instructors/experts contributed to student learning by providing a true picture reflection of happenings on the ground. Conclusion The importance of in-country African instructors’ can be viewed as that aimed at validating students’ ideas to apply to the local settings, streamlining students’ focus, providing a platform for multi-stakeholder engagement to a particular topic, coupled with bringing an in-country context experience in the classroom.